2014
DOI: 10.1105/tpc.113.121061
|View full text |Cite
|
Sign up to set email alerts
|

Fast Retrograde Signaling in Response to High Light Involves Metabolite Export, MITOGEN-ACTIVATED PROTEIN KINASE6, and AP2/ERF Transcription Factors in Arabidopsis    

Abstract: Regulation of the expression of nuclear genes encoding chloroplast proteins allows for metabolic adjustment in response to changing environmental conditions. This regulation is linked to retrograde signals that transmit information on the metabolic state of the chloroplast to the nucleus. Transcripts of several APETALA2/ETHYLENE RESPONSE FACTOR transcription factors (AP2/ERF-TFs) were found to respond within 10 min after transfer of low-light-acclimated Arabidopsis thaliana plants to high light. Initiation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
183
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(190 citation statements)
references
References 104 publications
(129 reference statements)
6
183
1
Order By: Relevance
“…2014). Mutants lacking TPT have previously been shown to be unable to acclimate to high irradiances (Walters et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2014). Mutants lacking TPT have previously been shown to be unable to acclimate to high irradiances (Walters et al .…”
Section: Discussionmentioning
confidence: 99%
“…2004. Rapid transient expression of transcription factors observed following an increase in irradiance is suppressed in the tpt2 mutant of Col‐0 (Vogel et al ., 2014). This suggests that cytosolic concentrations of triose phosphates and/or other primary metabolites are important in regulating gene expression in a highly dynamic way.…”
Section: Discussionmentioning
confidence: 99%
“…A subgroup of the AP2/ERF TF family is transcriptionally induced within 10 min after light shift. 15 Such rapid response systems serve as immediate reaction to counter the effects of fluctuating conditions and are important to allow for subsequent long term acclimation. Deep insight into early acclimation processes requires knowledge on the chronological order of events.…”
Section: -11mentioning
confidence: 99%
“…13,14 Recently, it has been shown that the predominant assimilate transporter, the triosephosphate-phosphate translocator (TPT), participates in rapid information transmission controlling transcript accumulation. 15 Rapid regulation relies on existing transcription factors (TF) which conditionally adjust gene expression in response to stress stimuli. 16 Downstream inducible TFs realize the acclimation response.…”
Section: -11mentioning
confidence: 99%
See 1 more Smart Citation